Hubungan Dukungan Ibu Dengan Kesiapan Remaja Putri Menghadapi Menarche Di SMP N II Sukoharjo - Yulia, Shinta; Surmiasih, S; Putri, Riska Hediya; Kameliawati, Feri (Wellness And Healthy Magazine, 2021)
Teenages is marked by the appearance of signs of puberty, puberty in young women is marked by hormonal changes that cause the first menstruation or called menarche. The average age at menarche for young women ranges from 10-19 years. In general, young women learn about menstruation from their mothers, but not all mothers provide adequate information about menstruation. The importance of maternal support in providing information about menstruation to young women, so that young women can recognize the signs and changes that occur so that young women have readiness to face menarche. This research objective was to determine the correlation between maternal support and the readiness of young women to face menarche at SMP N II Sukoharjo.This type of research is quantitative with correlational method with cross sectional approach. The research was conducted at SMP N II Sukoharjo on 19-20 February 2021. The population in this research was all of the seventh grade on young women at SMP N II Sukoharjo who had not experienced menstruation as many as 48 students and made the total population of the research. Data collection tools to measure maternal support and readiness in this research were in the form of a questionnaire. Bivariate data analysis used the gamma statistic test.The results showed that the maternal support for young women on facing menarche was mostly positive, namely 29 young women (60.4%), Readiness of young women in facing menarche was positive, namely 41 young women (85.4%). Gamma statistic results obtained p-value = 0.001, it can be concluded that there is correlation between maternal support and the readiness of young women to face menarche at SMP N II Sukoharjo. It is expected that mothers can provide more adequate information about menstruation to their daughters so that young women are better prepared to face their first menstruation.ABSTRAK  Masa remaja ditandai dengan kemunculan tanda-tanda pubertas, pubertas pada remaja putri  ditandai dengan perubahan hormonal yang menyebabkan datangnya menstruasi pertama kali atau disebut menarche. Rata-rata umur menarche remaja putri berkisar 10-19 tahun. Pada umumnya, remaja putri belajar tentang menstruasi dari ibunya, tetapi tidak semua ibu memberikan informasi yang memadai tentang menstruasi. Pentingnya dukungan ibu dalam memberikan informasi tentang menstruasi kepada remaja putri, sehingga remaja putri dapat mengenali tanda-tanda dan perubahan yang terjadi agar remaja putri memiliki kesiapan dalam menghadapi menarche. Penelitian ini bertujuan untuk mengetahui hubungan dukungan ibu dengan kesiapan remaja putri menghadapi menarche di SMP N II Sukoharjo. Jenis penelitian ini adalah kuantitatif dengan metode korelasional dengan pendekatan cross sectional. Penelitian dilakukan  di SMP N II Sukoharjo pada tanggal 19-20 februari 2021. Populasi dalam penelitian ini adalah seluruh remaja putri kelas VII di SMP N II Sukoharjo yang belum mengalami menstruasi sebanyak 48 siswi dan dijadikan total populasi penelitian. Alat pengumpulan data untuk mengukur dukungan ibu dan kesiapan pada penelitian ini berupa kuesioner. Analisa data bivariat menggunakan uji statistik gamma.Hasil penelitian diperoleh dukungan ibu pada remaja putri dalam menghadapi menarche sebagian besar positif, yaitu sebesar 29 remaja putri (60,4%), Kesiapan pada remaja putri dalam menghadapi menarche positif, yaitu sebesar 41 remaja putri (85,4%). Hasil statistik gamma didapat p-value = 0,001, dapat disimpulkan ada hubungan dukungan ibu dengan kesiapan remaja putri menghadapi menarche di SMP N II Sukoharjo. Diharapkan ibu dapat memberikan informasi yang lebih memadai tentang menstruasi kepada putrinya agar remaja putri lebih siap dalam menghadapi menstruasi pertamanya.